Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/elan.200403216
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin and (±)-Taxifolin Electrochemical Oxidation Mechanisms

Abstract: The electrochemical behaviour of the flavone chrysin and the dihydroflavonol (AE)-taxifolin was investigated by different electrochemical techniques at different pH values. Dihydroflavonol (AE)-taxifolin presented two oxidation peaks. The first electrooxidation reaction of (AE)-taxifolin is reversible over the whole pH range. The dependence of peak current on pH showed a maximum around neutral pH values with a decrease in acidic and alkaline media. The influence of the catechol group deprotonation on ring B is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…The electrochemistry of this selected series of synthesized coumarinnaphthalene-stilbene hybrids (6)(7)(8)(9)(10) showed that the difference in the position of the hydroxyl substituents have only a slightly effect upon the electroactivity of the selected coumarins.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The electrochemistry of this selected series of synthesized coumarinnaphthalene-stilbene hybrids (6)(7)(8)(9)(10) showed that the difference in the position of the hydroxyl substituents have only a slightly effect upon the electroactivity of the selected coumarins.…”
Section: Discussionmentioning
confidence: 97%
“…The phenol group is irreversibly oxidised in compounds 6, 7, 8, and 10, and the catechol group is reversibly oxidised in compound 9. The oxidation products of the coumarin-naphthalene-stilbene hybrids (6)(7)(8)(9)(10) The monohydroxylated compounds 6-8, irreversible pH-dependent oxidation process, occurs with one electron and one proton transfer, following the phenol oxidation mechanism [43]. Compound 6, with the para position to the hydroxyl group occupied, formed a single oxidation product corresponding to a catechol moiety, Scheme 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations